Sex-Dependent Improvement in Survival of Parkinson's Disease Patients - Kuusimäki T; Kurki S; Sipilä JOT; Salminen-Mankonen H; Carpén O; Kaasinen V (WILEY, 2022)
Background Advances in the treatment of Parkinson's disease (PD) and changes in general life expectancy may have improved survival in patients with PD.Objective The objective of this study was to investigate recent trends in PD mortality.Methods In total, 1521 patients with PD in local and national registries were followed for 11 years (2006-2016) from diagnosis until exit date or death, and the causes of death were recorded.Results The survival of men with PD improved during the follow-up period, but no change was observed in women (2-year postdiagnosis survival in men, 79.0%-86.3%, P = 0.03; 2-year postdiagnosis survival in women, 82.8%-87.5%, P = 0.42). Pneumonia was the most common immediate cause of death.Discussion The survival of men with PD has improved in Finland without a similar change in women. Because changes in treatment likely affect both sexes similarly, the results may reflect the decreasing sex gap in life expectancy. This phenomenon will likely increase the already high male-to-female prevalence ratio of PD.